STRUKTUR IKLAN KOMERSIAL DI MEDIA CETAK MESIR (STRUCTURE OF COMMERCIAL ADVERTISEMENT IN EGYPT PRINTED 126 MEDIA) - Moh. Masrukhi, Syamsul Hadi, Suhandano, Thoyib (CMES (Center of Middle Eastern Studies), 2014)
Commercial advertisement of the printed media usually appears in two kinds. There are verbal and compounding of verbal and nonverbal.  The article explores thestructure of commercial advertisement of the printed media in Egypt. The objective ofthis paper is to explain the elements and the patterns in each structure.  It collectedadvertisement from Egypt news papers and magazines during April until June 2013 andanalyzed the data using the theory of advertisement of Leech and Bathia. The analysisresult reveals that verbal structure has more patterns than nonverbal ones. It concludesthat the verbal structure is more complex than nonverbal structure and its existence isneeded to help verbal messages.